Diagnostic Accuracy of Ultrasound and Correlation with Surgical Outcomes in Children with Undescended Testes - Malik, Huma; Farooq, Omama; Zafar, Tania; Iqbal, Tooba; Zafar, Muhammad Tayyab; Shah, Syed Khurrum Hussain (Biological and Clinical Sciences Research Journal, 2025)
Cryptorchidism, or undescended testes (UDT), is a common congenital anomaly in male infants with potential implications for fertility and malignancy if not treated promptly. Ultrasound (US) is frequently employed for preoperative localization, but its diagnostic performance remains variable. Objective: To evaluate the diagnostic accuracy of ultrasound in localizing undescended testes in pediatric patients and to correlate sonographic findings with intraoperative surgical outcomes. Methods: A prospective diagnostic accuracy study was conducted at a tertiary care hospital in Pakistan from February to April 2025. Seventy-eight male children (aged 6 months to 10 years) with clinically suspected UDT underwent high-resolution ultrasound imaging before surgical exploration. Ultrasound findings were compared to intraoperative observations, which served as the gold standard. Diagnostic parameters, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, were calculated. Concordance rates between ultrasound localization and surgical findings were analyzed. Results: Among the 78 enrolled patients, 109 testes were evaluated. The mean age was 3.6 ± 1.8 years; 60.3% of cases were unilateral. Ultrasound demonstrated a sensitivity of 88.9%, specificity of 82.1%, PPV of 93.5%, NPV of 71.9%, and overall diagnostic accuracy of 87.1%. Concordance with intraoperative findings was highest for inguinal testes (96.5%), followed by abdominal (85.7%) and non-palpable testes (66.7%). False negatives were more common in intra-abdominal and atrophic testes. Conclusion: Ultrasound offers high sensitivity and diagnostic accuracy for localizing undescended testes, particularly in the inguinal region. However, its limitations in identifying intra-abdominal or non-palpable testes suggest a need for adjunct imaging modalities, such as diffusion-weighted MRI, to improve diagnostic precision and surgical planning. A multimodal imaging approach is recommended for complex or ambiguous cases to optimize clinical outcomes.